1997
DOI: 10.1021/jp962932o
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Conformational Analysis of 1,4-Dioxane

Abstract: The inversion of 1,4-dioxane has been studied by using ab initio molecular orbital theory at the HF/6-31G* and BLYP/6-31G* levels. A total of 10 stationary points were characterized as energy minima or transition states. Vibrational frequencies were calculated for the chair and two twist-boat conformations. The chair conformation is the lowest in energy, followed by the two twist-boats. The transition state connecting the chair and the twist-boats is a half-chair structure, in which four atoms in the ring are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 19 publications
7
41
0
Order By: Relevance
“…[32][33][34][35] On the one hand, THF has a relatively flat 5-member ring that possesses puckering out of the planar configuration, with the flatness of this ring structure producing a number of conformations that lie close in energy. Further, low potential energy barriers for pseudo-rotation between its conformations enable essentially free rotation between minima.…”
Section: Structure and Spectroscopy Of Cyclic Ethersmentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34][35] On the one hand, THF has a relatively flat 5-member ring that possesses puckering out of the planar configuration, with the flatness of this ring structure producing a number of conformations that lie close in energy. Further, low potential energy barriers for pseudo-rotation between its conformations enable essentially free rotation between minima.…”
Section: Structure and Spectroscopy Of Cyclic Ethersmentioning
confidence: 99%
“…32,33 On the other hand, it has been well established that both THP and 1,4-dioxane exist in their lowest energy chair conformations. 34,35 These, respectively, have C s and C 2h symmetries. In the interest of making fruitful comparisons regarding the behavior of these three cyclic ethers, we consider THF through an average over the C 2 to C s conformations; with experimental results having revealed that both conformations exist in near equal proportions at roomlike temperatures.…”
Section: Structure and Spectroscopy Of Cyclic Ethersmentioning
confidence: 99%
“…20 -22 An interesting feature of the Raman spectra of liquid dioxane are very weak bands at 634, 555, 523 and 274 cm 1 . According to an ab initio study, 23 there exist several other conformations of dioxane in addition to the most stable one, the chair. In order of increasing energy of formation, the two closest in energy to the chair structure are 2,5 twist boat, (symmetry C 2 ), and 1,4 twist boat (symmetry D 2 ), both 31.2 kJ mol 1 higher in energy.…”
Section: Normal Coordinate Analysismentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Although the conformational analysis of cyclohexane and substituted cyclohexanes have been extensively studied, [5][6][7][8][9][10]16,17 comparatively few computational studies have been reported on the conformers and ring reversal mechanisms of unsubstituted diheterocyclohexanes. [11][12][13][14] There are computational studies on stereoelectronic hyperconjugative interactions in the chair conformers of diheterocyclohexanes, 9 -14,17-25 but no reports concerning the various other conformers and the ring interconversion mechanisms of 1,4-dithiacyclohexane [1,4-dithiane, 1; eqs. (1), (2) and (3)].…”
Section: Introductionmentioning
confidence: 99%